Prolegomena to ubuntu and any other future South African philosophy - Prinsloo, Aidan Vivian (Rhodes University, Faculty of Humanities, Department of Philosophy, 2014)
In this thesis I consider ubuntu as a metonym for the particularly African features of South African philosophy. Given that Mbembe critiques African philosophy in general as having failed because it has been subsumed under two unreflective political movements in African thought, I consider whether or not the concept of ubuntu escapes his critique. After developing criteria for measuring the success of any philosophical concept, I conclude that ubuntu is unsuccessful. I then identify the political constraints placed on ubuntu that lead to its failure. These constraints arise from having to validate Africa as a place of intellectual worth. Considering the role of place in these constraints, I argue that a far more productive approach to ubuntu (and South African philosophy in general) is to explicitly incorporate this place into our philosophical project. I use the conceptual framework developed by Bruce Janz to provide a systematic account of place that can be used in formulating South African philosophy. I add to Janz, arguing that philosophy is a response to a particular feature of place: the mystery. By incorporating place into ubuntu, I am able to start developing a philosophical concept which can fulfil the political constraints placed on ubuntu without sacrificing its philosophical integrity. I suggest that ubuntu remains an interesting concept primarily because it promises to respond to the fragmentation of the South African place. I conclude by arguing that ubuntu should be used as the basis for a civic religion which responds to the fragmentation of the South African place. This civic religion will give rise to a significantly distinct philosophical tradition which should not succumb to Mbembe's critique.
Keywords: Ubuntu (Philosophy); Political science -- Philosophy; Philosophy, African; Social values -- South Africa; Social values -- South Africa -- Philosophy; Place (Philosophy)